Analisis Pengaruh Rekam Medis Elektronik Berdasarkan Teori TAM - Firmansye Ika Panggulu; Rokiah Kusumapradja; Lily Widjaja (Jurnal Health Sains, 2022)
Electronic medical records are computerized health information systems that provide detailed records of patient demographic data, medical history, allergies, and history of laboratory examination results and some of which are also equipped with decision support systems. The purpose of the study was to analyze the influence of organizational contextual factors, attitudes and social influences simultaneously and respectively on the application of electronic medical records. Method: The model used to test the acceptance of technology is the Technology Acceptance Model (TAM). This study uses a quantitative approach with explanatorical causality research design with a sample of 65 with individual analysis units. Tenik data retrieval with questionnaires and tested with path analysis. Results: Based on the results of the above research can be summarized that the findings in this study are in line with TAM theory with variables of contextual factors of organization, attitudes and social influences affect the perception of benefits and perception of ease in electronic medical records both individually and simultaneously. In addition, contextual factors of the organization affect social influence but attitudes do not affect social influence. Implication: This research assists hospital management in developing this electronic medical record system to be easier to use by creating a network of systems that can be accessed on mobile phones by the PPA even if they are not in the hospital. recognize the importance of management support and training in the application of electronic medical records